Systemic Urate Deposition: An Unrecognized Complication of Gout? - Khanna, Puja (J Clin Med, 2020)
Gout, an inflammatory arthritis, affects over nine million people in the US with increasing prevalence. Some medical societies do not recommend treating gout unless it is recurrent. While soft tissue urate deposits (tophi), resultant bone erosions, and joint inflammation are frequently recognized in gout, urate crystal deposits in other sites have been thought to be rare. Recent diagnostic testing, such as dual energy computed tomography (DECT), has led to the recognition that urate deposits are not uncommon in other tissues including the vasculature. To understand the potential risks for untreated gout, we reviewed the literature on extra-articular urate deposition documented by autopsy, histopathology, surgery, and radiology, including the heart, blood vessels, kidney, spine, eye, skin, and gastrointestinal system. These studies extend the significance of gout beyond the rheumatologist and emphasize the need for physicians to follow the American College of Rheumatology guidelines to treat subjects with gout to a goal of achieving serum urate <6 mg/dl. Given the growing body of literature on extraarticular urate deposition, further studies and clinical trials are needed to determine the clinical consequences of systemic urate deposition, including if reducing cardiac and vascular urate deposits may provide a survival benefit for this at-risk population.